Pengembangan sentra penjualan dan desain kemasan untuk meningkatkan nilai tambah tanaman hias - Ferdiansyah Ali; Yahya Dewanto; Budi Suyanto (Institut Seni Indonesia Yogyakarta, 2023)
Ciwalen Village, Sukaresmi District, Cianjur Regency, has the potential to become a center of economic growth as a floricultural village, not just to supply ornamental plants to Jakarta. Conditions like this are very profitable for owners of large land areas and with large capital. Another case is for farmers with limited land and small capital. They are only scattered among small traders selling ornamental plants on the sides of the road, only with a small amount of paper or plastic packaging. In this study, the aim was to establish a sales center and develop packaging designs. With the existence of a sales center, it is hoped that the sales system will be more focused and effective, as well as a solution to concentrate sales information on ornamental plants. The development of packaging design can expand the market share of ornamental plants. With an attractive and very personal packaging design, it will provide added value to ornamental plant products. The method used in this research is a qualitative research method that is inductive analysis. The research method consists of collecting, compiling, and describing various actual data, documents, and information. The discussion results show that the existence of sales centers, besides becoming a tourist destination, can also increase the selling value of ornamental plants. Meanwhile, product packaging increases the emotional appeal and influences purchasing decisions for ornamental plants.